The Sing Sing files : one journalist, six innocent men, and a twenty-year fight for justice - Slepian, Dan (Celadon Books, 2024)
"It wasn't the September 11 attacks or the murders he'd investigated for the NYPD that haunted him, the detective told journalist Dan Slepian, but a 1990 case where two men were sentenced to twenty-five years to life in prison for a murder they didn't commit. When Slepian, a veteran producer for NBC's Dateline, asked how he knew, the cop replied, "Because I know who the real killers are." Slepian couldn't shake what the detective had told him-and what it said about the criminal justice system. It began a two-decade-long personal and professional odyssey in which Slepian used his investigative skills to prove the innocence of not just those two men, but of four others also falsely convicted of murder by New York courts. The Sing Sing Files: One Journalist, Six Innocent Men, and a Twenty-Year Fight for Justice is Slepian's cinematic account of challenging a system fiercely resistant to rectifying or even acknowledging its mistakes and their consequences. The reader follows Slepian on prison visits, street reporting, and during his interactions with prosecutors, defense attorneys, witnesses, and police for the Dateline stories that eventually led to freedom for the imprisoned men. At the book's center is the friendship that developed between Slepian and Jon-Adrian "JJ" Velazquez, who, from his cell at Sing Sing, directed Slepian to other innocent men until he, too, was finally released in 2021 after serving decades in prison. Like Bryan Stevenson's Just Mercy, The Sing Sing Files is a powerful account of addressing wrongful imprisonment but in the nation's largest city, not the rural South. Slepian's extraordinary book, at once infuriating and full of hope, shines a light on an injustice whose impact the nation has only begun to confront"--